2006
DOI: 10.1177/112067210601600213
|View full text |Cite
|
Sign up to set email alerts
|

Central Serous Chorioretinopathy and Helicobacter Pylori

Abstract: The results of this study show that the prevalence of H. pylori infection seems to be significantly higher in patients with CSC than in control s. H. pylori infection may represent a risk factor in patients with CSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 14 publications
1
44
0
8
Order By: Relevance
“…Five patients with chronic CSCR served as a control group. The mean age of control patients was 44 years old (range, [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53], with the woman/man ratio being 1 : 4. The number of right and left eyes studied was also similar (3 right eyes and 2 left eyes).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five patients with chronic CSCR served as a control group. The mean age of control patients was 44 years old (range, [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53], with the woman/man ratio being 1 : 4. The number of right and left eyes studied was also similar (3 right eyes and 2 left eyes).…”
Section: Resultsmentioning
confidence: 99%
“…Several factors have been implicated in the initiation and development of this retinal disorder, including immunological reactions, toxins, infections, and neuronal, hormonal, or circulatory processes. [34][35][36][37][38] One theory suggests that there is a focal increase in the choriocapillaris permeability that causes damage to the overlying RPE, and it is suspected that the disturbance would originate in an alteration of the mechanisms of choroidal blood flow autoregulation. 39 An alternative hypothesis postulates that CSCR is provoked by a dysfunction of the RPE that, in turn, causes a reverse in fluid movement in a chorioretinal direction, leading to subretinal space leakage and retinal detachment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several investigators reported that the prevalence of Helicobacter pylori is high in patients with CSC [18].…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…At the moment, there are no new reports of this association in the medical literature possibly only because it is not being considered or investigated. However, it is worth recalling that antiphospholipid syndrome has been associated with other diseases of immunologic origin that in turn are associated with H. pylori infection, such as ITP [189,219,220], systemic lupus erythematosus [221], and central serous chorioretinitis [222,223].…”
Section: Antiphospholipid Syndromementioning
confidence: 99%